Analisis Sektor Ekonomi Unggulan Kabupaten Rejang Lebong di Provinsi Bengkulu - Bertha Iin Esti Indraswanti; Sunoto Sunoto (Convergence: The Journal of Economic Development, 2021)
The purpose of this research was to analyze the leading economic sectors of Rejang Lebong Regency. According to BPS secondary time series data (2014-2019), descriftive analysis was used for analyze the economic structure and leading economic sectors. Based on different approach, demand (PDRB) and supply (employment), this research was to determine the leading sectors. The result of this research can be concluded that Rejang Lebong Regency was an agriculture economy eventhough the leading economic sector was not that. It based on demand side approach differ by supply side. The first periods of 2014-2017, Rejang Lebong Regency has 9 leading sectors, and the second period of this research become 7 tercier sectors. It was used PDRB data, and become 4 leading sectors (primary and tercier sectors) when employment data used merely. When the data of PDRB and employment was combined to analyze the Rejang Lebong Regency economy, there were no same leading sectors. This condition indicated that the development of 7 sectors economy of Rejang Lebong Regency was driven by demand, not only local but also demand from other region demand.